2007
DOI: 10.1111/j.1365-313x.2007.03137.x
|View full text |Cite
|
Sign up to set email alerts
|

Identification of genes expressed in the Arabidopsis female gametophyte

Abstract: SummaryThe angiosperm female gametophyte typically consists of one egg cell, two synergid cells, one central cell, and three antipodal cells. Each of these four cell types has unique structural features and performs unique functions that are essential for the reproductive process. The gene regulatory networks conferring these four phenotypic states are largely uncharacterized. As a first step towards dissecting the gene regulatory networks of the female gametophyte, we have identified a large collection of gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

10
293
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 257 publications
(303 citation statements)
references
References 72 publications
10
293
0
Order By: Relevance
“…These results indicate that expression of the pBiP1::BiP1 construct complemented the defect in fusion of the polar nuclei, and that this defect arose from the bip1 bip2 double mutation. We produced BiP1 cDNA constructs driven by the promoters of various genes expressed in specific cells of the female gametophyte (15) and used the constructs to transform b1/+ b2/b2 plants. We found that BiP1 expression in the central cell, but not in other female gametophytic cells, suppressed the seed abortion phenotype (Table S3).…”
Section: Resultsmentioning
confidence: 99%
“…These results indicate that expression of the pBiP1::BiP1 construct complemented the defect in fusion of the polar nuclei, and that this defect arose from the bip1 bip2 double mutation. We produced BiP1 cDNA constructs driven by the promoters of various genes expressed in specific cells of the female gametophyte (15) and used the constructs to transform b1/+ b2/b2 plants. We found that BiP1 expression in the central cell, but not in other female gametophytic cells, suppressed the seed abortion phenotype (Table S3).…”
Section: Resultsmentioning
confidence: 99%
“…A primary transcriptomic comparison of UP, ovules, and siliques enriched the UP and ovule data sets for stage-specific transcripts by excluding common sporophyte-expressed genes potentially involved in carpel and ovule determination, such as SEEDSTICK (STK; Rounsley et al, 1995) and SHATTERPROOF1 (SHP1; Flanagan et al, 1996), a phosphogluconolactonase (At5g24420) that is expressed in ovule integuments and in the ovary wall (Scutt et al, 2003), as well as genes involved in later stages of seed development, such as MEDEA (MEA; Vielle-Calzada et al, 1999), FERTILIZATION INDE-PENDENT SEED2 (Luo et al, 1999), and FLOWERING WAGENINGEN (Kinoshita et al, 2004). Using the parameters outlined in "Materials and Methods" and further comparison with publicly available data sets (Zimmermann et al, 2004;Tung et al, 2005;Yu et al, 2005;Steffen et al, 2007;Borges et al, 2008;Wang et al, 2008;Qin et al, 2009;Wuest et al, 2010), a total of 42 genes were considered enriched or preferentially expressed in ovules (Supplemental File S1). As anticipated, 27 out of 42 transcripts preferentially expressed in ovules and 96 out of 1,275 ovule-enriched transcripts were previously reported to be expressed specifically in the embryo sac or enriched in female gametophytic cells (Supplemental File S1; Yu et al, 2005;Johnston et al, 2007;Punwani et al, 2007;Steffen et al, 2007;Wuest et al, 2010).…”
Section: Prediction Of Stage-specific and Reproductive Organ-enrichedmentioning
confidence: 99%
“…Using the parameters outlined in "Materials and Methods" and further comparison with publicly available data sets (Zimmermann et al, 2004;Tung et al, 2005;Yu et al, 2005;Steffen et al, 2007;Borges et al, 2008;Wang et al, 2008;Qin et al, 2009;Wuest et al, 2010), a total of 42 genes were considered enriched or preferentially expressed in ovules (Supplemental File S1). As anticipated, 27 out of 42 transcripts preferentially expressed in ovules and 96 out of 1,275 ovule-enriched transcripts were previously reported to be expressed specifically in the embryo sac or enriched in female gametophytic cells (Supplemental File S1; Yu et al, 2005;Johnston et al, 2007;Punwani et al, 2007;Steffen et al, 2007;Wuest et al, 2010). Ovule-expressed transcripts likely include plausible candidates for shortrange pollen tube attractants expressed in the embryo sac (Higashiyama et al, 2001(Higashiyama et al, , 2003Chen et al, 2007;Okuda et al, 2009) but also of other modulators expressed in the surrounding sporophytic tissues that could function as long-range pollen tube attractants.…”
Section: Prediction Of Stage-specific and Reproductive Organ-enrichedmentioning
confidence: 99%
See 1 more Smart Citation
“…To confirm that synergid degeneration was not properly executed upon pollen tube arrival by AP1G loss of function, we expressed NLS-YFP under a synergid-specific promoter Pro DD39 (27). Synergid nuclei were labeled in both unfertilized wild-type and ap1g/+ ovules ( Fig.…”
Section: Resultsmentioning
confidence: 98%